Real‐time temperature compensation for tunable cavity‐based BPFs and BSFs. Issue 6 (17th May 2018) - Wu, Yu‐Chen; Abu Khater, Mohammad; Peroulis, Dimitrios
Abstract : In this study, a real‐time temperature compensation control system for tunable high‐ Q cavity‐based filters are designed, implemented, and experimentally validated. Both bandpass (BPFs) (700–1000 MHz) and bandstop filters (BSFs) (1300–1600 MHz) with high‐ Q ( Q ≃ 400 ) resonators are monitored in real time to compensate for any temperature variations. The monitoring scheme includes additional resonators that share the same tuning piezoelectric actuators with the resonators of the radio frequency (RF) filters. An oscillator is coupled with each monitoring resonator resulting in an output signal at a frequency directly linked to the RF resonance. Each monitoring resonator is controlled by a user‐provided input through a closed‐loop in real time. The presented system is capable of compensating for temperature variations in the − 40 and 80 ∘ C range. The average system resolution varies from 0.23 to 9 MHz, depending on temperature, with a 1 ms sensing period. The closed‐loop frequency shift is 6.5 MHz (0.93%) and 8.75 MHz (0.65%) for the BPFs and BSFs, respectively, in the − 40 to 80 ∘ C temperature range. This is to be compared with the open‐loop change of 256 MHz (36%) and 590 MHz (44%) for the same temperature change. The monitoring oscillator power leakage to the RF cavities is optimised and measured to −101 dBm.